Phylogenetic study and association between prominent genotype and haplotype of KISS1 gene with FSH level in Idonesian native goat breeds - A. Febriana; S. Sutopo; E. Kurnianto; W. Widiyanto (Diponegoro University, 2021)
The aim of the current research was to analyze the population structure and expression of KISS1 gene associated with reproductive traits through Follicle Stimulating Hormone (FSH) level and DNA sequencing analysis based on KISS1 gene. Genotypes of 23 goat does consist of Kacang goats (n=7), Kejobong goats (n=8) and Senduro goats (n=8) were investigated using DNA sequencing, 16 out of 23 samples were synchronized to examine their FSH level using ELISA method. The data were analyzed using MEGA X software for DNA sequences and General Linier Model (GLM) for FSH plasma level. The phylogenetic tree showed the high homology between Indonesian native goats with other species showing a gene conservatism. A significantly higher FSH plasma levels were obtained from Kacang and Kejobong than Senduro goat (P = 0.002), litter size (LS) 3 than LS 1 (P = 0.0175), further CAATGCGCAACGCT haplotype and GA genotype at g.2459 G>A have a higher FSH plasma than other haplotypes and genotypes (P = 0.0027; P<0.0001) and are associated with high LS (3.0±0.18). Neither sample collection times nor parities have different significantly. The current trial indicated that CAATGCGCAACGCT haplotype and GA genotype at g.2459 G>A were correlated with reproductive traits.